1978
DOI: 10.1007/bf01869897
|View full text |Cite
|
Sign up to set email alerts
|

Electron microprobe analysis of frog skin epithelium: Evidence for a syncytial sodium transport compartment

Abstract: For elucidation of the functional organization of frog skin epithelium with regard to transepithelial Na transport, electrolyte concentrations in individual epithelial cells were determined by electron microprobe analysis. The measurements were performed on 1-micron thick freeze-dried cryosections by an energy-dispersive X-ray detecting system. Quantification of the electrolyte concentrations was achieved by comparing the X-ray intensities obtained in the cells with those of an internal albumin standard. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
69
3

Year Published

1980
1980
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(86 citation statements)
references
References 42 publications
14
69
3
Order By: Relevance
“…Furthermore, studies on the cellular distributions of Na + /K + -ATPase in the toad and turtle urinary bladders and frog skin have shown that the vast majority of Na + pumps are localised in the granular cells and that the intercalated MR cell possesses only a few of these pumps. This distribution pattern is consistent with the model that the granular cell compartment is responsible for Na + uptake (Rick et al, 1978;Durham and Nagel, 1986;Nagel and Dörge, 1996) and suggests that the few Na + pumps present in the intercalated MR cells are sufficient to maintain the balance of the Na + and K + gradients across the basolateral membrane but do not significantly contribute to Na + uptake.…”
Section: Models For Na + Uptake By the Branchial Epithelium Of Lampresupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, studies on the cellular distributions of Na + /K + -ATPase in the toad and turtle urinary bladders and frog skin have shown that the vast majority of Na + pumps are localised in the granular cells and that the intercalated MR cell possesses only a few of these pumps. This distribution pattern is consistent with the model that the granular cell compartment is responsible for Na + uptake (Rick et al, 1978;Durham and Nagel, 1986;Nagel and Dörge, 1996) and suggests that the few Na + pumps present in the intercalated MR cells are sufficient to maintain the balance of the Na + and K + gradients across the basolateral membrane but do not significantly contribute to Na + uptake.…”
Section: Models For Na + Uptake By the Branchial Epithelium Of Lampresupporting
confidence: 88%
“…This mechanism is dependent on the activities of both cytosolic carbonic anhydrase in the H + secreting cell and Na + /K + -ATPase in the basolateral membrane of the cell whose apical membrane contains the ENac (Harvey and Ehrenfeld, 1986;Harvey et al, 1988;Nagel and Dörge, 1996;Ehrenfeld and Klein, 1997). Furthermore, the toad and turtle urinary bladders, in which the epithelium has a cellular composition comparable with that of amphibian skin and consists also of granular cells and mitochondria-rich (MR) cells (Wade et al, 1975;Wade, 1976;Rick et al, 1978;Durham and Nagel, 1986;Brown and Breton, 1996), employ essentially the same mechanisms for reabsorbing Na + from the urine and for secreting H + into that urine (Stetson and Steinmetz, 1985;Durham and Nagel, 1986;Lang, 1988). In addition, the immunocytochemical demonstration that H + -ATPase and ENac are present in the gill epithelium of teleosts (Sullivan et al, 1995;Wilson et al, 2000a;Marshall, 2002) is consistent with the hypothesis that this mechanism for taking up Na + from a hypotonic environment is universal amongst vertebrates and invertebrates such as crustaceans, annelids and molluscs (Kirschner, 1983).…”
Section: Osmoregulatory Mechanisms In Freshwatermentioning
confidence: 99%
“…The polarity is maintained by the tight junctions between cells of the outer S. granulosum, which also restricts diffusion between the outer solution and the intercellular spaces (Martlnez-Palomo, Erlij, and Bracho, 1971). These structural observations, together with the demonstration of the syncytial behavior of the epithelium (Rick et al, 1978) and the large capacitance of the basolateral membrane of the intact epithelium (Smith, 1971 ;Garcia-Dfaz and Essig, 1985;Schoen and Erlij, 1985) indicates that, functionally, all innermost cell membranes behave as basolateral membrane. This implies that the majority of isolated cells will exhibit macroscopic properties that correspond to the basolateral membrane of the intact epithelium and there would be a much higher probability of recording single channels of basolateral origin/ One can also make the argument that, since the apical membrane of R. pipiens skin does not exhibit any significant conductive permeability to ions other than Na (Helman and Fisher, 1977;Nagel, 1977;Garcia-Diaz et al, 1985;Stoddard, Jakobsson, and Helman, 1985;D6rge, Beck, Wienecke, and Rick, 1989) the K and CI selective channels found in this study are necessarily of basolateral origin.…”
Section: Origin Of K and CL Channelsmentioning
confidence: 88%
“…Cells in this layer are joined by tight junctions (Farquhar and Palade, 1964) maintaining the epithelial polarity. Cells from all epithelial layers are interconnected by intercellular junctions, forming a syncytium (Farquhar and Palade, 1964;Rick, D6rge, Arnim, and Thurau, 1978). The inner membrane of the S. granulosum and all membranes of the innermost layers contain Na-K ATPase (Farquhar and Palade, 1966;Mills, Ernst, and DiBona, 1977) and, presumably, the K channels that confer high K selectivity to the basolateral membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have given clear evidence for the coupling in frog skins (20) while others have indicated very limited coupling (33). Current work by our group (R. Nielsen and H. H. Ussing, in preparation) indicates that both views may be correct, depending on the experimental circumstances.…”
Section: Coupling Between Cell Layersmentioning
confidence: 91%